Exploring The Impact of Mobile Banking Usage on Spending Habits: A Qualitative Study on Financial Overspending - Malini, Helma (Jurnal Keuangan dan Perbankan, 2025)
This study examines the influence of mobile banking on spending habits, focusing on its role in facilitating overspending. Utilizing a qualitative approach with an exploratory case study design, data were collected through in-depth interviews, focus group discussions, and document analysis to explore the interplay between mobile banking features and behavioral tendencies. The findings reveal a dual impact of mobile banking on financial behavior. On the positive side, mobile banking enhances financial awareness and discipline by providing tools such as real-time transaction monitoring, automated savings mechanisms, and budgeting features, enabling users to make informed decisions and maintain better control over their finances. However, the convenience and immediacy of mobile banking also present challenges, particularly the ease of completing transactions, which can encourage impulsive spending and reduce traditional psychological barriers to overspending. These insights highlight the need for targeted strategies to maximize the benefits of mobile banking while mitigating its risks. The study emphasizes the importance of designing responsible financial technologies and educational initiatives to promote disciplined financial behavior. Further research is suggested to explore the long-term effects of mobile banking usage on financial habits, including saving patterns, debt management, and overall financial health, with the goal of fostering a more financially resilient society.